Fixação de multas em liminares - Oliveira, Luciana Rodrigues de (2010)
The innovation of Article 461 of the Code of Civil Procedure brought new momentum to the process, giving it greater efficiency in court. Thus, the objective is to describe and analyze the fines and injunctions provisional execution. Thus, through the literature, it was possible to get the results indicate that the fine as a coercive measure that aims to serve the debtor on psychologically, causing him to voluntary compliance with the obligation to do so. In the end, it is considered that within the principle of proportionality and reasonableness that limit and determine the value of the fine, the court may provide the effectiveness of the process without requiring the debtor beyond the actual value of the fine and at the same time provide the lender collecting the financial obligation, such as the daily fine (astreinte). We will examine the major institute of astreinte, who every day have been used more by the judiciary to enforce its decisions on the obligations of do's and don'ts. The theme is not new, but still not well understood among lawyers and law enforcers. So try to solve some of the problems that have emerged as the outstanding legal disputes Before making remarks about the astreinte necessary, it is important to point out that part of the doctrine is wrong not only to define it, but also to address their consequences and their functions